PUBLIC TO PRIVATE MANAGEMENT BUY-OUTS: Causes and Effects - Mistry, Youhan (2008)
This paper provides an empirical study of 25 hand collected firms that went from being publicly traded corporations to private companies between 1997 and 2005. Data is derived from Sudarsanam et al. (2008, working paper) study titled, Going Private Buyouts and Private Equity: Bankruptcy Avoidance, Shareholder Gains and Turnaround. The research seeks to apply a traditionally lacking approach to the cause and effect study of management buy-outs. It is envisaged that significant insight has been missed out over the years as the more traditional quantitative approaches lack the richness of such a multi-faceted study. First, the 25 firms were grouped into two sets - one consisting of firms with a default probability of greater than 400 bps and the other with firms of lower probability of defaulting. The purpose of this study has been to identify and compare the causes leading to privatization among these firms followed by the comparison of their post buy-out effects. It was suggested by Sudarsanam et al. (2008, working paper) that high possibility of distress at the time of going private increases the chances of the target ending up in receivership. However, this was not the case among the set chosen for this study. Hence, this research seeks to identify the factors leading to the turnaround among the firms with high distress probability. The results were mainly driven by improvement in short term performance and efficiency